The Role of Media in the Agricultural and Rural Development of ACP Countries. Compilation Document - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2009)
Synthesis report of the CTA's 2009 Annual Seminar on the Role of the Media in Agricultural and Rural Development in ACP Countries.